2021
DOI: 10.1002/csc2.20534
|View full text |Cite
|
Sign up to set email alerts
|

Self‐fertility and resistance to the Colorado potato beetle (Leptinotarsa decemlineata) in a diploid Solanum chacoense recombinant inbred line population

Abstract: A diploid potato (Solanum tuberosum L.) recombinant inbred line population was derived from a cross between Solanum chacoense inbred line M6 and S. chacoense accession USDA8380‐1 (80‐1) to identify loci associated with self‐compatibility and Colorado potato beetle resistance. Individuals from the F4 and F5 generations were genotyped on the Illumina Infinium V3 22K Single Nucleotide Polymorphism (SNP) Array and a genetic map constructed. All F5 individuals contain at least one copy of the dominant S‐locus inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Among 2011 BC 2 individuals, we did not find any true recombinants in the 25.12 Mb interval on the short arm of Chromosome 6 ( Table S3 ). The suppression of recombination in this interval on Chromosome 6 is observed in many potato genetic maps, suggesting that this region is pericentromeric and that fine-mapping approaches will not reduce the size of the interval [ 16 , 43 , 54 , 55 , 56 , 57 ]. Thus, identification of the causal gene requires an alternative strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 2011 BC 2 individuals, we did not find any true recombinants in the 25.12 Mb interval on the short arm of Chromosome 6 ( Table S3 ). The suppression of recombination in this interval on Chromosome 6 is observed in many potato genetic maps, suggesting that this region is pericentromeric and that fine-mapping approaches will not reduce the size of the interval [ 16 , 43 , 54 , 55 , 56 , 57 ]. Thus, identification of the causal gene requires an alternative strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The Sli gene, which encodes an F-box PP2-B10 protein, is expressed in pollen and interacts with the maternal components of the gametophytic self-incompatibility (GSI) system, the S-RNases, during pollination, leading to a breakdown of the GSI system [ 13 , 14 ]. From a breeding point of view, this system works well and has resulted in the production of inbred lines in multiple programs [ 4 , 5 , 6 , 15 , 16 , 17 , 18 ]. However, as a consequence of the presence of Sli , maternal inbred lines are self-fertile, which necessitates emasculation for hybrid seed production.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have shown that traits that are selected for in tetraploid breeding programs, were also present in diploid potato germplasm [ 25 , 26 , 27 ]. Tuber shape was for instance mapped to the Ro locus with the round phenotype as the dominant effect [ 28 ], a finding confirmed by Meijer et al [ 26 ] and Jansky and Endelman [ 25 ] in diploid inbred populations.…”
Section: Inbred Line Developmentmentioning
confidence: 99%